Review of Gasification of Thermoplastics and Thermosets - Busto, Mariana (2025)
The end-of-life management of plastic represents a significant environmental challenge, largely due to its limited use, low biodegradability, and high volume of disposed material, in the order of 400 million tonnes by 2019. Several types of polymers can be recycled by mechanical means, but some others, like plastics, sometimes require chemical methods for their reuse. In this context, gasification is one of the most promising chemical recycling techniques. Gasification is a thermochemical process performed at moderate temperatures of work (800–1100 ◦C) that converts carbonaceous materials into rich hydrogen gas, which can be used for energy obtention or the Fisher–Tropsch process. However, this procedure can also produce undesirable by-products like tar and char. The products’ composition and relative quantities are highly dependent on the overall process configuration and the input fuel. The current study evaluates the catalytic gasification of the most common plastic waste, seeking to obtain higher gas yields and syngas with high energy. The text focuses on the current state of development and recent advances in various publications over the last fifteen years, with emphasis on thermoplastics and thermosets. The search showed that temperatures, the type of fluidizing gas, and the catalyst have a major influence on the quality of the obtained gas. Optimal gasification conditions, such as temperatures between 600 and 900 ◦C, depending on the plastic feedstock, steam-to-feedstock ratios > 1, the appropriate selection of a gasifying agent according to gas requirements and energy optimization, and the composition and location of the catalyst in the system (in situ, in the reactor, or ex situ), are identified as critical for maximizing H2 and CO production and minimizing tar. Finally, we provide summaries of the last advanced patent in the field, where the main focus appears to be feedstock pretreatment intended to ensure handling feasibility due to the variety of plastic wastes.